1998
DOI: 10.1016/s0022-5347(01)63100-8
|View full text |Cite
|
Sign up to set email alerts
|

SILDENAFIL, A TYPE-5 CGMP PHOSPHODIESTERASE INHIBITOR, SPECIFICALLY AMPLIFIES ENDOGENOUS cGMP-DEPENDENT RELAXATION IN RABBIT CORPUS CAVERNOSUM SMOOTH MUSCLE IN VITRO

Abstract: Sildenafil relaxes CCSM by amplifying the effects of the normal, endogenous cGMP dependent relaxation mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(45 citation statements)
references
References 22 publications
6
38
0
1
Order By: Relevance
“…In vitro studies using human and rabbit cavernosal smooth muscles show that sildena®l signi®cantly increases cGMP concentrations and augments relaxation responses in the presence of SNP, but has little or no effect on phenylephrine-induced contractions when the tissues are not exposed to SNP or electrical ®eld stimulation [17,18]. However, in the present study treatment with sildena®l signi®cantly relaxed rabbit cavernosal muscle in a concentration-dependent manner, as reported by Stief et al [5].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In vitro studies using human and rabbit cavernosal smooth muscles show that sildena®l signi®cantly increases cGMP concentrations and augments relaxation responses in the presence of SNP, but has little or no effect on phenylephrine-induced contractions when the tissues are not exposed to SNP or electrical ®eld stimulation [17,18]. However, in the present study treatment with sildena®l signi®cantly relaxed rabbit cavernosal muscle in a concentration-dependent manner, as reported by Stief et al [5].…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, Jeremy et al [20] reported that 10 mmol/L sildena®l alone increased the cGMP level up to ®ve-fold in rabbit corpus cavernosum tissue, and up to 28-fold in the presence of 1 mmol/L SNP. Reportedly, sildena®l alone signi®cantly reduced the basal tone in unstimulated rabbit cavernosal smooth muscle [18]. These in vitro and in vivo results suggest that signi®cant amounts of cGMP might be formed in the basal steady state in rabbit cavernosal smooth muscle.…”
Section: Discussionmentioning
confidence: 67%
“…PDE-5 catalyzes the breakdown of the cGMP and also reduces NO levels in the endothelial cells, thereby decreasing signalling (Boswell-Smith et al 2006). The use of PDE-5 inhibitors such as sildenafil, tadalafil and verdanafil does not only raise the levels of cGMP (Chuang et al 1998;Corbin 2004) but also stimulates activation of cGMP and increases NO bioavailability for the relaxation of penile tissue that results in penile erection. However, these inhibitors also elicit several side effects, including headache, dyspepsia, nasal congestion, visual abnormalities among others (Saxena et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Sildena®l, a widely prescribed oral medication for the treatment of male erectile dysfunction, is a selective and highly potent inhibitor of the type-5 cGMP-speci®c phosphodiesterase. 4 Type-5 PDE isozyme is predominantly expressed in the penile corpus cavernosum, however it has been localized in various other tissues, such as brain, lung, kidney and placenta. 5 Although little is known about the physiological role of PDE and its isoforms in human spermatozoa, its inhibition has been reported to stimulate sperm motility, suggesting an association between the levels of cytosolic nucleotides and sperm motion.…”
Section: Introductionmentioning
confidence: 99%